On the mode of uplift of the fish and fossiliferous moraines of the McMurdo Ice Shelf, Antarctica - Gow, Anthony Jack (Hanover, N.H. : U.S. Army Materiel Command, Cold Regions Research & Engineering Laboratory, 1965)
Mode of access: Internet.